THE MODERATOR ROLE OF AGE IN THE EFFECT OF HEDONIC CONSUMPTION BEHAVIORS ON CUSTOMER SATISFACTION (Third Sector Social Economic Review, 2020)
Businesses, whose main purpose is to satisfy consumer demands and needs, carry out activities and strategies to meet the expectations of consumers in marketing activities as well as production activities. It turns out that businesses that make an intense effort to meet the changing demands and needs of their target audience should meet the concrete needs of consumers as well as their abstract needs. Hedonic consumption behavior, which is considered as a purchasing behavior that addresses the feelings and feelings of consumers on the basis of their abstract needs rather than their concrete needs, is defined as a positive emotional experience that consumers experience. Hedonic consumption, which treats purchasing behavior as excitement, fun and pleasure, has a direct effect on customer satisfaction. However, age difference, which has a significant effect on purchasing behavior, is thought to have a moderator role in the relationship between hedonic consumption and customer satisfaction. Accordingly, the aim of this study is to determine whether age has a moderator role in the effect of hedonic buying behaviors on consumer satisfaction. A questionnaire was applied to the consumers in Konya with simple random sampling method. The data obtained from the survey were analyzed through the SPSS 23.0 package program and Process Macro was used to determine the moderator effect. As a result of the research, it has been determined that there is a positive and statistically significant relationship between consumers' hedonic buying behaviors and satisfaction levels. In addition, it was concluded that age has a moderator role in the effect of consumers' hedonic buying behaviors on satisfaction levels.
Keywords: Marketing; Consumer Behavior; Hedonic Consumption; Customer Satisfaction.